Design and Development of the ANTASENA Mobile-Based Emergency Reporting Application Using the Extreme Programming Method - Farhan Faturrachman; Imam Maruf Nugroho; Meriska Defriani (Universitas Mohammad Husni Thamrin, 2026)
The development of Android technology plays a vital role in handling emergency situations. The Fire and Rescue Department of Purwakarta Regency holds primary responsibility for firefighting, victim rescue, and disaster management, yet incident reporting is still conducted manually via WhatsApp, often resulting in imprecise address information that requires re-confirmation and delays emergency response. This research aims to design and build an Android-based mobile application named ANTASENA as a faster, more accurate emergency reporting solution, developed using the Kotlin programming language and Supabase cloud database, integrated with the Fonnte WhatsApp Gateway, applying the Extreme Programming (XP) method comprising the Planning, Design, Coding, and Testing phases. ANTASENA offers three key features: a digital reporting form with automatic location coordinate detection, integration of real-time disaster data from official sources such as BMKG, InaTews, Magma ESDM, Sipongi KLHK, and InaRiks BNPB, and a community feedback feature powered by the WhatsApp Gateway. Through this implementation, public reporting becomes faster, more efficient, and more accurate, as incident locations are detected automatically without repeated confirmation, so that ANTASENA is expected to accelerate the response of fire and rescue officers while enhancing public literacy and self-reliance in disaster mitigation within their community.